The independence of Scotland self-government and the shifting politics of union - Keating, Michael, 1950- (Oxford : Oxford University Press, 2009)
In a thought-provoking analysis Keating reviews the political, constitutional, and legal issues around Scottish independence and the political economy of independence surveying the options for a social and economic project for an independent Scotland.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Self-determination, National -- Scotland; Home rule -- Scotland; Scotland -- Politics and government -- 21st century